Rebels in Biblical and Chinese Texts: A Comparative Study on the Interplay of Myth and History - Amihay, Aryeh (Religions, 2020)
This study offers a new approach for studying biblical myth in two directions: first, by expanding the scope of investigation beyond the clearly mythological elements to other areas of biblical literature, and second, by drawing comparisons to classical Chinese literature. This article thus reconsiders the relationship between myth and history in both biblical and Chinese literature, while seeking to broaden the endeavor of the comparative method in biblical studies. Two examples are offered: (1) the story of Moses’s call narrative and his relationship with Aaron in Exodus in light of the story of Xiang Liang and Xiang Ji in the Shiji; (2) the story of Saul and David in 1 Samuel compared with the story of Dong Zhuo and Lü Bu in the Romance of the Three Kingdoms. Both comparisons demonstrate the operation of Claude Lévi-Strauss’s inversion principle. Conclusions regarding each of these literatures are presented separately, followed by cross-cultural insights and shared aspects in the study of myth, historiography, and religion.